1996
DOI: 10.3928/0148-4834-19960401-08
|View full text |Cite
|
Sign up to set email alerts
|

The Experience of Being a Male Student Nurse

Abstract: Although schools of nursing market their programs to all segments of society, men are underrepresented in schools of nursing. The purpose of this study was to identify male students' perceptions of the motivational factors, barriers and frustrations encountered in becoming a nurse. Eighteen students attended one of four focus groups representing one associate program, two baccalaureate programs and one diploma program. The students' belief that society perceived nursing as a feminine profession was an underlyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This study found some similar experiences as those reported in other studies. One similarity is the lack of progress toward inclusivity, as evidenced by participants reporting similar barriers as those reported in much older literature (Kelly et al, 1996;Poliafico, 1998;Villeneuve, 1994). However, findings from this study underscore several significant points of discussion that have not been reported or discussed elsewhere.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This study found some similar experiences as those reported in other studies. One similarity is the lack of progress toward inclusivity, as evidenced by participants reporting similar barriers as those reported in much older literature (Kelly et al, 1996;Poliafico, 1998;Villeneuve, 1994). However, findings from this study underscore several significant points of discussion that have not been reported or discussed elsewhere.…”
Section: Discussionsupporting
confidence: 66%
“…Participants cited lack of male nurse mentors in the academic and clinical workplace as a barrier for men in nursing. This finding was reported as much as three decades ago, which is evidence for a lack of progress for men in nursing (Kelly et al, 1996). However, it may be difficult to increase the presence of male mentors due to the low number of men pursuing nursing careers.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have found that male nurses and elementary teachers worried about being viewed as less masculine (Lupton, 2006), experienced “masculine role strain,” and received negative reactions from family and friends (e.g., Cross & Bagilhole, 2002; Cushman, 2005). Male nurses reported being stereotyped as unmanly and less able to provide nurturing care to patients (Kelly, Shoemaker, & Steele, 1996), as well as rejection from some patients (Kouta & Kaite, 2011). Male elementary school teachers worried about sexual misconduct accusations (O’Lynn, 2004).…”
mentioning
confidence: 99%
“…Male nurses, cabin crew, and elementary school teachers reported isolation, rejection (e.g., excluded from conversations and social activities), and tokenization (e.g., being asked to provide a “male” perspective during meetings) in their work (Sargent, 2001; Young & James, 2001). In the training environment, male nursing students reported being directed away from some specialties (e.g., obstetrics) and experiencing financial role strain (i.e., inability to be the primary income provider, lower socioeconomic status of nursing; e.g., Kelly et al, 1996; Smith, 2006). Male psychology students may face similar social and training barriers to their development, including internal conflict and/or perceived stigma as a man in a female-concentrated program due to their adherence to particular masculine ideology.…”
mentioning
confidence: 99%
“…They found that the family members had a significant impact on the choice of nursing as a career. The study of (Kelly et al, 1996) in Chicago reported that family members were the most encouraging forces to their entering nursing and was the main source of moral support during the years of schooling. These findings were confirmed, as the positive family reaction to join to the faculty of nursing represents (83%) of the subjects in this study.…”
Section: Discussionmentioning
confidence: 99%